1999
DOI: 10.1109/55.784459
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency dependence of channel noise in short-channel RF MOSFETs

Abstract: Using a two-dimensional (2-D) Green's function technique, similar to Shockley's impedance field technique, simulation results of the drain i d and gate induced i g channel noise are presented for an nMOS transistor as a function of frequency. The simulation results show that for frequencies much lower than the cutoff frequency of the transistor ft the correlation factor (i.e., i g i 3 d = i 2 g i 2 d ) between the drain and gate channel noise is equal to approximately 0.4j: For frequencies near the ft of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…It has been demonstrated that this method can be successfully used to predict noise in practical semiconductor devices. [11][12][13][14] It has also been shown [12][13][14] that conventional expression for the channel noise fails for short channel MOSFETs indicating that the nature of carrier transport and noise changes for short-channel MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that this method can be successfully used to predict noise in practical semiconductor devices. [11][12][13][14] It has also been shown [12][13][14] that conventional expression for the channel noise fails for short channel MOSFETs indicating that the nature of carrier transport and noise changes for short-channel MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Ο επαγόµενος θόρυβος πύλης είναι αµελητέος για µεγάλα ως και σχετικά µικρά στοιχεία αλλά µπορεί να γίνει σηµαντικός όταν οι διαστάσεις µικραίνουν σηµαντικά και η συχνότητα λειτουργίας είναι της τάξης των δεκάδων GHz. Μία έκφραση που περιγράφει την συγκεκριµένη πηγή θορύβου για υποµικρονικά στοιχεία έχει δοθεί [TRIANT97], ενώ τα ίδια ποσοτικά αποτελέσµατα µπορούν να βρεθούν αν προσεγγισθεί το ίδιο πρόβληµα µε συναρτήσεις Green [MANKU99γ].…”
Section: θερµικός θόρυβος καναλιούunclassified